A test of concordance between patient and psychiatrist valuations of multiple treatment goals for schizophrenia. (14th June 2011) - Bridges, John F. P.; Slawik, Lara; Schmeding, Annette; Reimer, Jens; Naber, Dieter; Kuhnigk, Olaf
Abstract Background While much discussion has been placed on the problem of poor compliance in the treatment of schizophrenia, there has been little discussion on the concordance between patients and psychiatrists, an important contributing factor to patient‐centred care. Objective To estimate the concordance between patients' and psychiatrists' (ordinal and cardinal) valuations of multiple goals for schizophrenia treatment and to illustrate the utility of the self‐explicated method in valuing a large number of treatment goals. Design Twenty treatment goals were identified during focus groups and literature review and were presented to patients and psychiatrists during structured interviews. Respondents were asked to rank the multiple treatment goals and rate them on a 5‐point Likert scale. Three scores were calculated based on the ranking (1–20), rating (Likert scale) (1–5) and a self‐explicated method estimated as the product of rating and ranking score (1–100). Concordance was tested using Spearman's rho for overall ordinal rankings and via anova and F‐test for the cardinal values assigned to a specific treatment goal. Participants A total of 105 outpatients diagnosed with schizophrenia and 160 psychiatrists in Germany. Results Patient and psychiatrist values were concordant when the ordinal properties of their valuations were assessed by rating (ρ = 0.63; P = 0.002), ranking (ρ = 0.51; P = 0.02) and self‐explicated methods (ρ = 0.54; P = 0.01). Significant discordances were found when comparing the cardinal value placed on any given treatment goal using all three approaches, but the self‐explicated method produced a more discerning statistic. Relative to patients, psychiatrists significantly (P < 0.05) overvalued reduced lack of emotion, improved sexual pleasure and improved communication while undervaluing reuptake of activities of daily living, improved satisfaction and recovered capacity for work. Conclusions While there is an overall concordance between patients' and psychiatrists' valuation, significantly different valuations on specific goals can be identified. Here, psychiatrists tend to focus on 'textbook' outcomes, while patients are more concerned with functioning and living a normal life. This study also demonstrates the importance of comparing the concordance in treatment goals and the importance of preference‐based methods, such as the self‐explicated method, in the study of concordance.